Investigation of Dry Herbage Yield and Some Quality Characteristics of Sorghum x Sudan Grass Hybrid Varieties Grown Under Semi-Humid Ecological Conditions - Halit TUTAR (ISPEC Journal of Agricultural Sciences, 2024)
This research was conducted in the 2019 and 2020 growing seasons to determine the most suitable sorghum x sudan grass hybrid variety or varieties in terms of dry herbage yield and quality characteristics in Bingöl, which has a semi-humid climate. Dry herbage yield (DHY), crude protein ratio (CP), acid detergent fiber (ADF), neutral detergent fiber (NDF), acid detergent lignin (ADL), dry matter digestibility (DMD), dry matter intake (DMI) and relative feed value (RFV) were determined for ten sorghum x sudan grass hybrid varieties grown in Bingöl University Faculty of Agriculture, Agricultural Application and Research Center according to coincidence blocks experimental design with 3 replications. In the varieties examined in the research, DHY varied between 12216-16397 kg ha-1, CP 5.15-8.15 %, ADF 39.43-45.85 %, NDF 51.45-62.89 %, ADL 9.20-13.15 %, DMD 53.18-58.18 %, DMI 1.91-2.33 % and RFV 78.68-104.30. According to the two-year combined averages, the Master BMR variety produced a higher dry herbage yield than the other varieties. Among the varieties, the highest CP, DMI, RFV, and the lowest NDF were obtained in the Master BMR variety. It was concluded that the Master BMR variety gave high values in terms of dry herbage yield and quality characteristics in Bingöl province's ecological conditions.